НАСТУПНІСТЬ У ВИХОВАННІ ВІДПОВІДАЛЬНОСТІ В СТАРШИХ ДОШКІЛЬНИКІВ І МОЛОДШИХ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2022)
The author describes the issues of effective implementation of continuity in the education of responsibility for children in preschools and primary schools.